The Association between Oral Hygiene and Gastric Pathology in Patients with Dyspepsia: a Cross-Sectional Study in Southeast Iran. - Zahedi, Leili; Jafari, Elham; Parizi, Molook Torabi; Shafieipour, Sara; Bakhsh Abbasi, Mehdi Hayat; Moghadam, Sodaif Darvish; Zahedi, Mohammad Javad (Middle East Journal of Digestive Diseases, 2017)
BACKGROUND Many studies have reported an association between periodontal infections and some systemic diseases such as respiratory and cardiovascular diseases. Some studies found a direct association between chronic gastritis caused by Helicobacter pylori (HP) infection and poor periodontal health. METHODS In a cross-sectional study from November 2014 to December 2015 in Kerman, the largest province in southeast Iran, patients with dyspepsia who were candidate for diagnostic upper gastrointestinal (GI) endoscopy were included in our study. Decayed, Missing, and Filled Teeth (DMFT) index and Loe plaque index that are two popular indexes in dental epidemiology were used to assess the oral health by a dentist before the upper GI endoscopy. According to the Loe plaque index, score: 0= no plaque, score: 1= a film of plaque attaching to the free gingival border and near area of the tooth, score: 2= moderate reposition of deposits within the gingival pocket, score :3= plenty of soft matter within the gingival pocket±on the tooth and gingival border. Scores ≤1, 2 and 3 equal to good, moderate, and poor oral hygiene, respectively. During upper GI endoscopy a total of six biopsy samples were taken from fundus, body, and antrum. A pathologist reported these samples according to Sidney's classification into superficial gastritis, atrophic gastritis, intestinal metaplasia, and dysplasia. RESULTS According to Sidney's classification 77 (89.5%) patients had superficial gastritis, 3 (3.5%) had atrophic gastritis, and 6 (7%) had intestinal metaplasia. HP was found in 80.2% of the gastric mucosal biopsy samples. There were not statistically significant relationship between Sidney's classification, presence of HP in gastric mucosal biopsies, and hygiene indicators (p>0.05). No relation was found between the DMFT index and superficial gastritis, atrophic gastritis, and intestinal metaplasia (p>0.05). Gastric infection with HP was found in 70%, 75%, and 100% of patients with mild, moderate, and sever DMFT index, respectively. CONCLUSION Our study showed that there might be a relation between poor oral hygiene and gastric precancerous lesions. In addition, HP infection in gastric histopathology might be associated with periodontal disease.